1997
DOI: 10.1152/jappl.1997.82.3.738
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal stimulation by hydrochloric acid causes neurogenic inflammation in the airways in guinea pigs

Abstract: To investigate whether tachykinins are released in the airways in response to stimulation of the esophagus, we studied the airway plasma extravasation induced by intraesophageal HCl in the presence or absence of neutral endopeptidase inhibitor phosphoramidon and NK1-receptor antagonist FK-888 in anesthetized guinea pigs. The airway plasma leakage was evaluated by measuring extravasated Evans blue dye in the animals pretreated with propranolol and atropine. Infusion of 1 N HCl into the esophagus significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
73
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 33 publications
2
73
0
1
Order By: Relevance
“…Airway plasma extravasation was abolished by capsaicin in rabbits, in agreement with previous results obtained in guinea pigs by HAMAMOTO et al [12]. These authors also demonstrated that this effect was inhibited in the guinea pig by the tachykinin NK 1 receptor antagonist, FK 888.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Airway plasma extravasation was abolished by capsaicin in rabbits, in agreement with previous results obtained in guinea pigs by HAMAMOTO et al [12]. These authors also demonstrated that this effect was inhibited in the guinea pig by the tachykinin NK 1 receptor antagonist, FK 888.…”
Section: Discussionsupporting
confidence: 91%
“…This effect is abolished in animals treated with capsaicin, a drug that induces a depletion of tachykinins from sensory nerves, or by the tachykinin NK 1 receptor antagonist FK 888. As these effects were observed in animals pretreated with atropine and propranolol and were abolished by bilateral vagotomy, HAMAMOTO et al [12] suggested that HCl effects in that airway involve nerve pathways in the periphery.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The concept of acid stimulation of distal oesophageal receptors activating an oesophageal±tracheobronchial reflex has gained wider support [29]. The lung and the gut, having a common embryological origin, share a similar neural supply, the vagus nerve, and recent studies have described neurogenic inflammation in the lungs of guinea-pigs after instillation of acid into the distal oesophagus [30]. Biopsy of skin after calcitonin gene-related peptide injection reveals an eosinophilic infiltration [31] and it is recognized that substance P has a degranulating effect on eosinophils [32].…”
Section: Discussionmentioning
confidence: 99%